Is export diversification good for profitability? First evidence for manufacturing enterprises in Germany - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This paper uses a tailor-made newly available data set for enterprises from manufacturing industries in Germany to investigate for the first time the links between export diversification over destination countries and goods on the one hand and the profitability of the exporting firms on the other hand. We find that profits tend to be larger in firms with less diversified export sales over goods and in firms with more diversified export sales over destination countries.
Keywords: F14; 330; Exports; diversification; profitability; Germany